2022
DOI: 10.2965/jwet.22-056
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Temperature Downshift Influences on Anaerobic Digestion in the Treatment of Municipal Wastewater Sludge

Abstract: Operating temperature significantly affects biogas output, process stability, and microbial communities involved in anaerobic digestion. There are several unanswered questions regarding how microbial communities adapt in correlation with biogas production performance, especially when a digester fails to maintain thermophilic conditions. In this study, long-term lab-scale anaerobic digestion was carried out using two fed-batch reactors at 55°C, with subsequent decreases in temperature to 48°C and 45°C. Within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Nevertheless, the biogas production decreased after the temperature was gradually downshifted and upshifted within 100 days of incubation for each temperature shift. These findings were supported by previous studies that showed a considerable decrease in biogas production (mainly CH 4 ) when the reactor was given a shock temperature raise [13,20,40] and a temperature decrease [8,41,42], despite the different thermal changing methods and source of inoculum and substrates used in these studies.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Nevertheless, the biogas production decreased after the temperature was gradually downshifted and upshifted within 100 days of incubation for each temperature shift. These findings were supported by previous studies that showed a considerable decrease in biogas production (mainly CH 4 ) when the reactor was given a shock temperature raise [13,20,40] and a temperature decrease [8,41,42], despite the different thermal changing methods and source of inoculum and substrates used in these studies.…”
Section: Discussionsupporting
confidence: 87%
“…In the AD process, the temperature changes significantly influence the abundance and the species of microbial communities, which may also impact biogas production [7][8][9]. Previously, we attempted to investigate the effect of temperature upshifts [7] and downshifts [8] using a similar method as demonstrated in the present study. However, the microbiome analysis was briefly performed, and the intercorrelation between microbial communities during temperature shift conditions was not widely elucidated.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations